FAKTOR GAJI, REMUNERASI, DAN PELATIHAN DALAM KEPUASAN TENAGA KEPENDIDIKAN NON-PNS SELAMA MASA PANDEMI COVID 19 DI UNIVERSITAS BRAWIJAYA - Sri Sunarmi; Moh. Bukhori; Yunus Handoko (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
The institutions or organizations wanted to get their employee’s work satisfaction at the highest level so that it would make a good impact on the result and goals themselves. The objective of this research was to analyze the effect of salary, remuneration, and training on the job satisfaction of non-public employees at the head office of Universitas Brawijaya during the pandemic. This research method was a quantitative approach with number sample of this study was 53 respondents to non-public employees using the non-probability sampling technique with accidental sampling, the analysis used multiple linear analysis techniques. The result showed that salary (X1) and remuneration (X2) have the most significant effect, but it’s opposite to the training (X3). In conclusion, the three points above give simultaneous effect to the non-public employees’ satisfaction